INTERACTIVE WORD WALLS IN TEACHING VOCABULARY AT THE NINTH GRADE OF SMP IT PANCOR KOPONG IN ACADEMIC YEAR 2014-2015 - Fikni, Zahratul (Universitas Hamzanwadi, 2015)
The objective of this research was to find out the whether using interactive word wall for the ninth grade of SMP IT Pancor Kopong in academic year 2014-2015 is effective or not in teaching vocabulary. The research design of this study used pre-experimental in one group pretest – posttest design to know students’ skills in vocabulary. The participants of the research were the ninth grade of SMP IT Pancor Kopong consists of 20 students. The research instrument used by the writer was vocabulary test, the kinds of test were multiple choice, fill the blank, and matching the word. The data of this research were mainly gathered through the test, pre test and post test. The pre test was administrated to see the students’ ability in vocabulary mastery before used interactive word wall strategy. The post test was administrated to see the students’ progress in vocabulary mastery. After the data were collected, the researcher then analyzed them by using t test formula. The finding of the research showed that: mean score of pre test was 60.25, while mean score of post test was 73.45, and observed was 6.94. the table with df=n-1 (20-1=19) and significance level at 0.05 was 2.31. Based on the data analysis, the alternative hypothesis of this research was accepted because tobserved was higher than ttable (6.94>2.31).it can be concluded that teaching vocabulary using interactive word wall was effective to improve the students vocabulary mastery